2018
DOI: 10.1111/aen.12330
|View full text |Cite
|
Sign up to set email alerts
|

How blind are they? Phototactic responses in stygobiont diving beetles (Coleoptera: Dytiscidae) from calcrete aquifers of Western Australia

Abstract: Subterranean water beetles endemic to groundwater calcretes of Western Australia exhibit convergent traits typical of troglomorphic arthropods, including loss of eyes, pigmentation and wings. As these dytiscid species are estimated to have been isolated underground in permanent darkness for over three million years, it is predicted that they will completely lack phototactic responses. We tested this hypothesis by analysing the behaviour of six subterranean beetle species within an observational arena with dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…5 ) suggest that other explanatory variables are involved. Whilst light would appear to be a poor candidate explaining the distribution of blind stygobionts, negative phototaxis, as suggested by the results in the present study, has also been observed in anophthalmic stygobiont beetles Paroster macrosturtensis from Australian calcrete aquifers 28 . Evidence of this behavior is supported by observations of T. pearsei in the cenote pool at Nohmozon occurring only at night.…”
Section: Discussionsupporting
confidence: 47%
“…5 ) suggest that other explanatory variables are involved. Whilst light would appear to be a poor candidate explaining the distribution of blind stygobionts, negative phototaxis, as suggested by the results in the present study, has also been observed in anophthalmic stygobiont beetles Paroster macrosturtensis from Australian calcrete aquifers 28 . Evidence of this behavior is supported by observations of T. pearsei in the cenote pool at Nohmozon occurring only at night.…”
Section: Discussionsupporting
confidence: 47%
“…The first possibility is the difference in their ecological niches. The calcrete aquifer, in which subterranean diving beetles live, is located at a depth of 10–30 m underground [11, 47]. In contrast, the upper hypogean zone, in which T. kuznetsovi adults live, is a few or some dozen centimeters below the slope surface of a v-shaped valley.…”
Section: Discussionmentioning
confidence: 99%
“…via adaptive processes or a relaxation of purifying selection 36 . The latter scenario is plausible as P. macrosturtensis is also known to have retained the ability to detect light despite inhabiting an aphotic environment for over ~ 3 million years 80 .…”
Section: Discussionmentioning
confidence: 99%